Housing Satisfaction of The Indonesian Adolescents - Tiara Putri Ananta Poli; Joko Adianto (International Journal of Built Environment and Scientific Research, 2022)
This study aims to understand the determining factors of housing satisfaction of the Indonesian adolescent, who are potential homebuyers. It investigates the factors of housing satisfaction in multi-stages, such as the socio-demographic attributes and housing attributes. It assists to unveil the distinctive and prominent housing attributes for the residents, according to their determining socio-demographic attributes for housing satisfaction in a quantitative method. From the collected 534 respondents, age and monthly income are the pivotal socio-demographic factors of housing satisfaction. Location and neighborhood are the housing norms with constant factorial attribute to housing satisfaction across the age and monthly income groups. While space and expenditure are varies in both groups. These findings also provide a general understanding of the important physical and social features of each housing norm to meet the housing satisfaction of the residents.